Liquidity in green power markets – An international review. (October 2018) - Frei, Fanny; Loder, Allister; Bening, Catharina R.
Abstract: The success of green electricity promotion hinges, among other things, on the liquidity in green power markets, i.e. how easy it is for market participants to trade green power in the market. This study reviews archetypes of green power markets worldwide with regard to market liquidity. Additionally, it identifies mechanisms through which trading characteristics, namely the dominant trading channel and the dominantly traded product, can influence liquidity in green power markets. The study finds that trading on an exchange platform or via brokers can foster liquidity better than bilateral trading. Also, trading spot or forward products can better support liquidity in green power markets than trading long-term contracts. Highlights: Liquidity in green power markets differs substantially worldwide. Market liquidity is influenced by trading characteristics. The employed trading channels and the dominantly traded product are relevant. More centralized dominant trading channels can foster liquidity. Trading short-term products supports market liquidity.